PENGARUH PENDAYAGUNAAN ZAKAT PRODUKTIF TERHADAP KESEJAHTERAAN MUSTAHIK - Moh Afiq Amiruddin; Muttaqin, Aminullah Achmad (Islamic Economics and finance in Focus, 2023)
This study aims first to analyze the level of mustahik welfare provided by BAZNAS Tulungagung Regency, then the second to analyze the effect of independent variables, namely the adequacy of zakat funds, guidance and supervision, as well as the allocation of zakat utilization on the dependent variable, namely mustahik welfare. The approach method used is quantitative and the data used is primary data obtained from the field through questionnaires. This study used a sample of 80 respondents from 143 mustahik who received productive zakat assistance by BASNAZ Tulungagung Regency. The data was tested using validity and reliability tests. Then descriptive analysis is carried out and tools are used to analyze from the data obtained from multiple linear regression analysis. Meanwhile, to test the hypothesis, a probability value test tool is used that will measure the correlation probability value. The results showed that the adequacy of funds, guidance and supervision, as well as the allocation of zakat utilization all have a significant influence on the welfare of mustahik.